Espacio y vanguardias artísticas - López Vílchez, Inmaculada (Arte, Individuo y Sociedad, 2007)
It has been one hundred years since the apparition of the Modern mouvements, this work pretends to show a before and an after of the representation of space that supposes the definitive negation of the picture, learned as window, named for Alberti into the Renaissance, that tries to supplant the object´s absence through itself fidelity. It ´s not just a change of the work formal appearance; above all, it establish a rupture of the same concept of representation that denies the subjection to the normativity. It conferes an special attention to the main system of spatial representation used for the artists until today, based on the conical perspective, that feignes to the news procedures and the innovating concepts that generates the work of art. This article goes deep into the relationship of the formal and conceptual aspects that plans the traditional model rupture, taking a real and symbiotic point of departure the destruction and the reconstruction of the characteristic model of European Occident, based on the Renaissancist perspective.